Grassland management: case study of vegetation characteristics and grazing systems in Mongolia plateau (Mongolian Journal of Agricultural Sciences, 2015)
Mongolian Plateau is an important component of the Eurasian steppe biological communities, located in the eastern inland plateau in Central Asia. Results of pearson correlation analysis of biomass, coverage, litter, perennial grasses proportion and excellent forages proportion showed aboveground biomass had positive correlation with litter, perennial grasses and excellent forages proportion (P < 0.05)in main types in Mongolian Plateau. According to the investigation of soil and vegetation basic characteristics, proportion of grasses in Mongolia, and Inner Mongolian steppe is similar, respectively Buriad. The optimization for grassland vegetation refreshment and pasture animal husbandry becomes complex due to self-frangibility and severe damage of typical grassland ecosystem. The traditional patterns of movement remained in Mongolia where the open access grazing systems allows having long distance of movement and using large grazing land. While in Buriatia with kolkoz and Inner Mongolia under the private property right the grazing area is limited. The Eastern Mongolia still holds the traditional nomadic herding and seasonally grazing grassland utilization ways which has not change in a wide range of grassland degradation yet. The research results shows indicate that high benefit of management pattern should be on the basis of nomadic system.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 100-105